Att växa i lekmiljöer - Gråhed, Jenny (2008)
The preschool constitutes a big part of many children's everyday existence. Its contents are therefore of great importance and the environment deserves a well thoughtout design. In this study, surveys in field and literature have resulted in conclusions around how plants can be used in children's play environments, in order to contribute to the experiencerelated values. The aim is to present conclusions to lean on when drawing up designproposals for new playgrounds, especially where the natural conditions are not so favorable. The first question that is responded to is how plants can be used in order to enrich the children's play environments. The next question is what can be done to make these plantings endure the activities.